Accuracy of zero-heat-flux thermometry and bladder temperature measurement in critically ill patients - Anselm Bräuer (Nature Portfolio, 2020)
Abstract Core temperature (TCore) monitoring is essential in intensive care medicine. Bladder temperature is the standard of care in many institutions, but not possible in all patients. We therefore compared core temperature measured with a zero-heat flux thermometer (TZHF) and with a bladder catheter (TBladder) against blood temperature (TBlood) as a gold standard in 50 critically ill patients in a prospective, observational study. Every 30 min TBlood, TBladder and TZHF were documented simultaneously. Bland–Altman statistics were used for interpretation. 7018 pairs of measurements for the comparison of TBlood with TZHF and 7265 pairs of measurements for the comparison of TBlood with TBladder could be used. TBladder represented TBlood more accurate than TZHF. In the Bland Altman analyses the bias was smaller (0.05 °C vs. − 0.12 °C) and limits of agreement were narrower (0.64 °C to − 0.54 °C vs. 0.51 °C to – 0.76 °C), but not in clinically meaningful amounts. In conclusion the results for zero-heat-flux and bladder temperatures were virtually identical within about a tenth of a degree, although TZHF tended to underestimate TBlood. Therefore, either is suitable for clinical use. German Clinical Trials Register, DRKS00015482, Registered on 20th September 2018, http://apps.who.int/trialsearch/Trial2.aspx?TrialID=DRKS00015482 .